Millennials alumni and donor behaviour: an insight from management-based university in Malaysia - Shaari, Hasnizam; Yong, Phoon Lee; Md. Salleh, Salniza; Perumal, Selvan; Zainol, Fakhrul Anwar (Inderscience Enterprises Ltd., 2019)
Recent economic crisis had dragged not only profit-oriented organisations into hard situation, non-profit organisations such as public universities in Malaysia also badly affected especially in term of limited budget allocation from government. Hence, public universities are facing tremendous challenge in sustaining their university performance especially in sustaining their ranking and reputation at the global arena. As a result, universities in Malaysia nowadays are encouraged to be more creative in wealth creation for financial sustainability. This study attempts to investigate alumni readiness to donate to their alma maters as a part of the financial sustainability agenda among public universities. The study among 311 millennials alumni from one of the well-known management-based university in Malaysia revealed that attitude towards donation, peer pressure and religiosity play a significant role in explaining donor behavioural intention. Besides, religiosity also found to mediate the relationship between attitude towards donation and donor behavioural intention. Implication and recommendation for future research also is discussed in this article.